Technical and Operational Assessment of Stand-Alone Photovoltaic (SAPV) Systems - Rhaif , Raheem H. (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
These years, the deterioration of the environment has been aggravated by desertification, fast depleting water resources, and extraordinary occurrences of drought. Accordingly, standalone photovoltaic (SAPV) systems have been a tactical way to provide effective isolated power, especially for isolated areas that lack adequate infrastructural facilities. PVSYST is a sophisticated software simulation tool for modeling, simulating, and evaluating the performance behavior of a photovoltaic (SAPV) system. The current research work aims to develop an integrated method to assess the energy productivity efficiency and technical performance effectiveness of a photovoltaic (SAPV) system by employing PVSYST software simulation. This simulation method combines high-resolution geographic data and appropriate user-designed system module layout concepts to achieve optimal system sizing, thereby maximizing production efficiency to a higher extent by incorporating various system performance optimization techniques to improve technical efficiency and economical viability. The use of simulation software for SAPV system design improves SAPV system designs and ensures a complete analysis of total energy transfer. The simulation result authenticates that PVSYST software is an accurate system for simulating daily, monthly, and annual energy production and is a potent tool for designing sustainable, economical, and efficient solar power setups for isolated areas of Iraq.